Inmate-on-Inmate Prison Violence in Chile: The Importance of the Institutional Context and Proper Supervision - Sanhueza, Guillermo E. (Journal of interpersonal violence, 2021)
In this article, using a quantitative approach, we analyze interpersonal, inmate-on-inmate physical violence in Chilean prisons, using administrative records on collective violence, provided by the Prison Service for the period 2014 to 2017. Violence behind bars is problematic as it threatens inmates’ fundamental rights such as personal safety but also because it undermines efforts to maintain an environment prone to inmates’ social reintegration. Our data showed a sharp increase in the number of collective fights, from 808 in 2014 to more than 4,000 in 2017. In terms of the predictors, being in a private prisons as well as a greater ratio of inmates to guards were associated with increased collective fights for each of the 4 years we examined. Two additional predictors were statistically significant, yet only for 2017: A higher average criminal involvement score and a smaller ratio between inmates/staff were both associated with increased violence. Despite the fact that prison violence has not yet reached the scale or level of brutality that can be seen in other parts of the region (i.e., Brazil), there are signs of concern that authorities should take into account, particularly the rapid increase in collective fights in just a 4-year period and the recent social turmoil that has taken place in Chile, whose impact cannot be seen yet from these data. In terms of recommendations, we suggest that authorities should prioritize efforts in four areas: (a) to gather better data on prison violence, including some reliable data on importation variables (age, criminal history, and nationality); (b) to provide prison guards with tools to anticipate and mediate conflicts; (c) to revise and possibly modify the way prisoners are transferred to different facilities, and (d) in sum, to promote prison environments that can be more legitimate and supportive to inmates’ reintegration.